Co-benefits in building retrofit : methodology proposal, tool development and a case-study demonstration - Almeida, Manuela Guedes de (2013)
The existing building stock encloses a huge potential for actions to deal with climate change and to move towards a sustainable economy, but the decision making process for its renovation keeps hampered by the evaluation of building renovation measures that only considers the direct costs, disregarding other relevant benefits and thus, significantly underestimating the full value of improvement and re-use of buildings, both in local and global economy. The goal of this study was to identify a broader scope of effects that arise from building renovation and to propose a methodology for their quantification and integration in the decision making process in order to assist owners and promoters in the definition of the most appropriate renovation measures. These effects that arise from building renovation operations have been related with the different packages of renovation measures in order to allow comparing and ranking them through a tool developed for this purpose. The application of the developed methodology and tool to a case study allowed to confirm the relevance of the non-financial benefits in the final evaluations, proving that not only economic criteria should support decisions in the field. An enormous influence of the categories related to the social aspects was demonstrated, as well as to the environmental parameters, clearly showing that these parameters can change the ranking between the tested renovation packages.